Reaksi Pasar terhadap Pernyataan Resmi Badan Pemeriksa Keuangan terkait Mega Skandal Jiwasraya - Asih, Ethya Tre Widhy; Dewi, Ni Wayan Yulianita (Universitas Pendidikan Ganesha, 2021)
This study was focused to discover how was the effect of official statement of audit board related to Jiwasraya scandal on market reaction. Variables used in this study were abnormal return, trading volume activity, and security return variability. Population in this study were all companies which registered in Indonesia stock exchange and selected by using purposive sampling technique so the sample used were 45 companies in LQ45 index. The data used in this study was secondary data and collected by documentation and internet research. This study used quantitative method by paired t-test and Wilcoxon test in SPSS application. The result indicates that there was significant difference of abnormal return, trading volume activity, and security return variability before and after official statement of Audit Board related to Jiwasraya scandal. It showed that official statement of Audit Board consisted of bad news that caused the reaction of market.Â